O Ideb e as políticas educacionais em municípios do Caparaó Capixaba - Ribeiro, Welison Carlos Loiola (2022)
The Basic Education Development Index (Ideb) is one of the main indicators of quality in Basic Education in Brazil and is established as a reference instrument for the elaboration of educational policies. In this context, this study analyzed how the Ideb results are linked to the educational policies of some municipalities in CaparaóES (Ibitirama, Muniz Freire and Iúna), in the period from 2007 to 2019. Therefore, it is based on the contributions of authors such as Chirinéa. Höfling, Gatti, Alavarse, Soares, Gusmão and Silva for the development of the work. It is a qualitative research, of the case study type. As a data collection instrument, a document consultation and a semi-structured interview with the municipal education secretaries were used. For data analysis, content analysis was chosen. A critical look was also launched on the use of IDEB as the main reference for quality in education, considering its limitations, when addressing the aspects that constitute quality education and the contexts in which education is developed. In addition to historically and socially contextualizing the events that contributed to the IDEB, as well as the evaluation policies, to become quality references in recent years. It was concluded that IDEB has an influence on the educational management of the analyzed municipalities, especially because it is an instrument of political and social pressure, but in general, it does not reflect the managers' concept of quality education. Despite recognizing the limitations of Ideb as a reflection of educational quality, the secretaries of education also see themselves in the role of working so that the index will always increase and reach its goals, either to improve the municipality's position in the Ideb ranking, or for purposes or to obtain funding for the school/municipality. It was also observed how the managerial aspects, which make up neoliberal concepts and influence public policies and management, are presented in the analyzed education departments.